2013
DOI: 10.3989/gya.133112
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the protein concentration process from residual peanut oil-cake

Abstract: The objective of this study was to find the best process conditions for preparing protein concentrate from residual peanut oil-cake (POC). The study was carried out on POC from industrial peanut oil extraction. Different protein extraction and precipitation conditions were used: water/ flour ratio (10:1, 20:1 and 30:1), pH (8, 9 and 10), NaCl concentration (0 and 0.5 M), extraction time (30, 60 and 120 min), temperature (25, 40 and 60 °C), extraction stages (1, 2 and 3), and precipitation pH (4, 4.5 and 5). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The protein content of the concentrate was 72.80%. This was lower compared with the average of 79.36% protein content obtained from groundnut flour at pH 8-10 ( Gayol et al, 2013). The difference may probably be due to differences in extraction pH (Garba & Kaur, 2014).…”
Section: Proximate Composition Of Gpcmentioning
confidence: 67%
See 2 more Smart Citations
“…The protein content of the concentrate was 72.80%. This was lower compared with the average of 79.36% protein content obtained from groundnut flour at pH 8-10 ( Gayol et al, 2013). The difference may probably be due to differences in extraction pH (Garba & Kaur, 2014).…”
Section: Proximate Composition Of Gpcmentioning
confidence: 67%
“…First, the beany flavor of many legumes often results in low acceptability (Mune, Minka, & Mboma, ). Second, there is the problem of poor digestibility of leguminous crops owing to the presence of oligosaccharides which are not easily digested (Gayol, Pramparo, Nepote, Fernendez, & Grosso, ). Consequently, proteins in legumes/nuts are of poor quality and low biological value (Garba & Kaur, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gayol et al . () observed peanut oil cake and peanut concentrate with high percentages of Asp, Glx, and Cys + Val + Met. Amino acid composition reported for others raw materials commonly used in the preparation of biodegradable films, showed Glx (9.11%) and aspartic acid (5.91%) as the major amino acid in defatted soy flour and, Glx (12.48%) and Arg (6.73%) in cottonseed flour (USDA, ).…”
Section: Resultsmentioning
confidence: 94%
“…However, when full‐fat peanut flour was used, the protein content (PP) of the final extracted product was 77%, probably due to the presence of oil in the feedstock. The high oil content reduced the efficiency of protein extraction due to the formation of emulsions with protein during extraction (Gayol and others ). The final PY calculated as the ratio between final and initial solids (PY, Table ) indicated that the defatted soybean flour gave almost twice the yield (37.2%) compared to the peanut counterpart (19.4%).…”
Section: Resultsmentioning
confidence: 99%